2014
DOI: 10.1016/j.electstud.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Growth trajectories in the strength of party identification: The legacy of autocratic regimes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The study contains various samples, such as separate Eastern German and refreshment samples; however, we limit our analysis to West German citizens. We exclude East Germans and immigrants as the nature of partisanship and political attitudes differs for these groups due to their different socialization experiences (Kroh 2014; Neundorf 2009).…”
mentioning
confidence: 99%
“…The study contains various samples, such as separate Eastern German and refreshment samples; however, we limit our analysis to West German citizens. We exclude East Germans and immigrants as the nature of partisanship and political attitudes differs for these groups due to their different socialization experiences (Kroh 2014; Neundorf 2009).…”
mentioning
confidence: 99%
“…While the middle‐aged are more likely to engage in politics and develop strong partisan identities, interest in politics diminishes in the later stages of life, producing a curvilinear relationship between age and partisanship. Overall, empirical research tends to corroborate the ‘experience hypothesis’, namely that the predominant pattern is one in which partisan attachments become stronger as voters get older (Kroh, 2014; Dassonneville, 2017).…”
Section: Why and How Age Period And Cohort Can Influence Indecision A...mentioning
confidence: 99%
“…As such, the socialization perspective proposes that overtime changes occur primarily through the replacement of existing voters by new generations that are shaped by the political environment during their early life (e.g., Hooghe, 2004;Mannheim, 1964;Ryder, 1965;Tilley, 2005). Indeed, many studies have demonstrated how generational replacement can bring about political change (e.g., Bhatti and Hansen, 2012;Kroh, 2014;Neundorf and Niemi, 2014;Van der Brug and Kritzinger, 2012). However, it has not yet been examined if generational replacement is also responsible for the changing ideological correlates left-right identification in Western Europe.…”
Section: Introductionmentioning
confidence: 99%